Formulation of SrO-MBCUS Agglomerates for Esterification and Transesterification of High FFA Vegetable Oil - Prashant Kumar; Anil Kumar Sarma; Ajay Bansal; Mithilesh Kumar Jha (Bulletin of Chemical Reaction Engineering & Catalysis, 2016)
Musa Balbisiana Colla Underground Stem (MBCUS) catalyst was treated thermally mixing with 5:1 w/w of Strontium Oxide (SrO) and the dynamic sites were reformed. The MBCUS-SrO showed sharper crystalline phases as evidence from XRD and TEM analysis. The composition and morphology were characterized from BET, SEM, EDX thermo-gravimetric analysis (TGA) and XRF analysis. The optimization process for biodiesel production from Jatropha curcas L oil (JCO) having high percentage of free fatty acids was carried out using orthogonal arrays adopting the Taguchi method. The linear equation was obtained from the analysis and subsequent biodiesel production (96% FAME) was taken away from the JCO under optimal reaction conditions. The biodiesel so prepared had identical characteristics to that with MBCUS alone, but at a lower temperature (200˚C) and internal vapour pressure. Metal leaching was much lower while reusability of the catalyst was enhanced. It was also confirmed that the particle size has little impact upon the conversion efficacy, but the basic active sites are more important.